2006
DOI: 10.1097/01.ta.0000196379.74305.e4
|View full text |Cite
|
Sign up to set email alerts
|

National Nosocomial Infection Surveillance System: From Benchmark to Bedside in Trauma Patients

Abstract: Compared with strict bacteriologic criteria for VAP, the NNIS definition has good overall agreement and seems to have utility as an epidemiologic benchmarking tool in trauma patients. However, the NNIS definition has less utility as a bedside decision-making tool in this population, leading to under-treatment in a significant number of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 13 publications
(15 reference statements)
1
33
0
Order By: Relevance
“…Also in our study, the kappa values were poor between physicians' diagnoses and the other two methods; 0.42 for B and 0.49 for C. It has been recently shown, when three infection control reviewers retrospectively analyzed cases by CDC criteria (criterion B) in pneumonia surveillance, that the kappa value for identification of VAP among 50 patients suspected to have VAP was only 0.40 [26]. In another study, among 292 trauma patients, the kappa value between CDC criteria and quantitative bronchoalveolar lavage (BAL) was high, 0.73 [27]. Although both methods gave almost identical numbers of VAP cases (200 by CDC and 189 by BAL), 32 cases were positive with CDC and negative by BAL, and 30 positive cases by BAL were missed by the second method.…”
Section: Discussionmentioning
confidence: 95%
“…Also in our study, the kappa values were poor between physicians' diagnoses and the other two methods; 0.42 for B and 0.49 for C. It has been recently shown, when three infection control reviewers retrospectively analyzed cases by CDC criteria (criterion B) in pneumonia surveillance, that the kappa value for identification of VAP among 50 patients suspected to have VAP was only 0.40 [26]. In another study, among 292 trauma patients, the kappa value between CDC criteria and quantitative bronchoalveolar lavage (BAL) was high, 0.73 [27]. Although both methods gave almost identical numbers of VAP cases (200 by CDC and 189 by BAL), 32 cases were positive with CDC and negative by BAL, and 30 positive cases by BAL were missed by the second method.…”
Section: Discussionmentioning
confidence: 95%
“…20,21 However, a study of patients in our institution indicated that, while specific patients may differ, the rates of pneumonia were similar whether bronchoscopic or National Healthcare Safety Network criteria were used. 22 While this study was designed to be powered to detect a 50% reduction in the VAP rate, this was predicated on a historical VAP rate of 5.8 Ϯ 1.47 per 1,000 ventilator days, present in early 2010 during study planning. The observed baseline rate was only 3.29/1,000 ventilator days.…”
Section: Discussionmentioning
confidence: 99%
“…Successful extubation was defined as remaining free of mechanical ventilation until discharge. Nosocomial pneumonia was defined according to the National Nosocomial Infections Surveillance System (NNIS) definition [25]. Systemic infection was defined as presence of fever, white blood cell count >12,000, and positive blood, urine, or sputum cultures without other identified cause of fever and elevated white blood cell count.…”
Section: Definitionsmentioning
confidence: 99%